Asigurarea dreptului copilului la familie: prioritate națională [Articol] - Marginean, Livia (CEP USM, 2021)
The content of this article examines the situation of children left without parental care, a concern that requires attention and imperative in the actions of government representatives, public authorities at all levels and in all sectors, international institutions and organizations, civil society representatives, because the right of many children to family remains unmet. Based on recent studies demonstrating the harmful effects of separation and the residential care for children, we support and argue the importance of prompt interventions by social actors aimed to protect children and to ensure their rights, especially the right to family.
ENSURING THE RIGHT OF THE CHILD TO THE FAMILY: A NATIONAL PRIORITY
Keywords: prevention of institutionalization; family reintegration; intersectoral cooperation; alternative family services; deinstitutionalization; intersectoral mechanism